2022
DOI: 10.1242/jeb.216440
|View full text |Cite
|
Sign up to set email alerts
|

Global change and physiological challenges for fish of the Amazon today and in the near future

Abstract: Amazonia is home to 15% (>2700, in 18 orders) of all the freshwater fish species of the world, many endemic to the region, has 65 million years of evolutionary history and accounts for 20% of all freshwater discharge to the oceans. These characteristics make Amazonia a unique region in the world. We review the geological history of the environment, its current biogeochemistry and the evolutionary forces that led to the present endemic fish species that are distributed amongst three very different water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 165 publications
0
5
0
Order By: Relevance
“…The effects of climate change, which result in the global decline of biomass and changes in distribution patterns, diversity, and reproduction [ 64 , 65 ] of aquatic resources [ 66 , 67 ], are factors that have raised concerns in the Amazon region. The increase in temperature leads to changes in precipitation patterns and prolonged dry periods, reducing water discharge and the consequent productivity of the Amazon River [ 68 ]. These alterations are likely to favor aquatic species with high thermal tolerance [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of climate change, which result in the global decline of biomass and changes in distribution patterns, diversity, and reproduction [ 64 , 65 ] of aquatic resources [ 66 , 67 ], are factors that have raised concerns in the Amazon region. The increase in temperature leads to changes in precipitation patterns and prolonged dry periods, reducing water discharge and the consequent productivity of the Amazon River [ 68 ]. These alterations are likely to favor aquatic species with high thermal tolerance [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in temperature leads to changes in precipitation patterns and prolonged dry periods, reducing water discharge and the consequent productivity of the Amazon River [ 68 ]. These alterations are likely to favor aquatic species with high thermal tolerance [ 68 ]. Recent studies have found that elevated temperatures in coral reef regions can accelerate the growth of Lutjanidae larvae, but survival rates are lower [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Amazonian ecosystem has an important role in the conservation of biodiversity and the regulation of the global climate because it is home to the largest rainforest, which has been intensively devastated [1,2]. The maintenance and conservation of biodiversity have been the biggest challenges in the last few decades [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Deforestation in the Amazon promotes environmental degradation and consequently the reduction in species and natural resources in the region [8]. During 2022, the increase in deforestation in the Brazilian Amazon was about 12,480 km 2 , presenting an increase of 2.3% compared to 2021 (12,188 km 2 ) [9]. The rainforest is highly heterogeneous and considered a complex system, which makes it difficult to conduct species monitoring and to obtain more information about mortality, growing and natural regeneration, and climate change impacts [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation